Effect of scleral lens use on conjunctival microbiota. Issue 2 (April 2020) - Dogan, Cezmi; Bahar Tokman, Hrisi; Mergen, Burak; Arslan, Osman Sevki; Iskeleli, Guzin
Highlights: Scleral lens use was linked to an increase in the culture negativity. The most commonly observed microorganism was S. epidermidis in the scleral lens users. The second most commonly observed microorganism was S. aureus in the scleral lens users. Scleral lens use was linked to a decrease in the culture positivity with S. epidermidis in comparison to the control group. Abstract: Aim: This study aimed to investigate the effect of scleral lens (SL) use on conjunctival microbiota. Method: A total of 26 eyes of 26 patients using an SL and 25 eyes of 25 healthy controls were included in the study. The samples were obtained from the lower fornices of the eyes using sterile swabs. For the bacteriological examination, a bacterial culture was obtained by inoculating the samples on chocolate agar, blood agar, MacConkey agar, and fluid thioglycollate medium. After 24–48 h of incubation at 37 0 C, the growth of different colonies of bacteria was identified using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (Bruker MALDI Biotyper). Results: The mean age of the study group was 41.6 ± 19.1 years (18–65); the mean age of the control group was 40 ± 6 (21–62) (p = 0.69). There were 10 male patients and 16 female patients in the study group and 9 male patients and 16 female patients in the control group (p = 0.86). The mean duration of SL use was 13.7 ± 13.4 months (1–42 months). No bacterial growth was observed in 17 (65.4 %) of the 26 eyes in the SL group and 5 (20 %) of the 25 eyes in the control group (p = 0.001). The most commonly observed microorganisms were Staphylococcus epidermidis ( S.epidermidis ) and Staphylococcus aureus ( S.aureus ) in both groups. Conclusion: SL users were found to have a higher rate of culture negativity in comparison to the healthy controls, suggesting that SLs have a significant effect on conjunctival microbiota.